From research behaviour to cognitive- research activity - Odintsova G. A., Ryaposova S. V. (Modern education development theory techniques and practice, 2016)
in this article the author investigates the possibility of digital microscope use while working with children of primary preschool age, contributing to passing of research behavior into cognitive-research activity.
Keywords: исследовательская деятельность; исследовательское поведение; познавательное развитие; младшие дошкольники; Research activity; research behavior; цифровой микроскоп; cognitive development; junior preschoolers; digital microscope